A brief summary of the biophysical aspects of magnetotactic bacteria and their relationship to astrobiology through terraforming (Research, Society and Development, 2020)
Magnetotactic bacteria are gram negative, capable of responding to magnetic fields and have interesting characteristics related to their biophysical and metabolic versatility. The aim of this research is to suggest that these microorganisms, due to these characteristics, may participate together in the terraforming process with other photosynthetic extremophilic microorganisms. Magnetotactic has a cosmopolitan distribution and is ubiquitous in microaerobic aquatic environments. Although magnetotactic bacteria are historically related to the ALH 84001 meteorite as a species of biosignature or as a possible fossil record from Mars, this problem will not be addressed in this paper. A brief review of the magnetotactic bacteria and how they may be related in a possible terraforming process on Mars or other planets will be briefly presented. Finally, it is important to emphasize that this theme has evolved greatly over time, from a science fiction story to a truly scientific domain and context. Finally, it is hoped that this work will serve as motivation and basis for future research in order to contribute to the spread of astrobiology.